Successful evolution of software systems - Yang, Hongji (Artech House software engineering library., 2003)
Annotation Explores the feasibility of using techniques such as program transformation and program abstraction to re-engineer and extend the life of an existing IT system. The authors (De Montfort University) outline a program transformation-based evolution workbench called FermaT, the architecture of the wide spectrum language (WSL), and a process for evolving object-oriented, real-time, and parallel systems. The final chapter presents six case studies that use FermaT and re- engineering assistant tools to evolve from source code to specifications or to new source code in a different language. Annotation copyrighted by Book News, Inc., Portland, OR.